Kegiatan Yayasan Setelah Berlakunya Undang-Undang Nomor 16 Tahun 2001 tentang Yayasan di Daerah Istimewa Yogyakarta - Mr. Sularto (Fakultas Hukum Universitas Gadjah Mada, 2009)
This research is meant to examine the foundations activities, especially the ones concerning with the implementation of the adjustment of the foundation’s statutes and their constraints as well as their entries which are in accordance with the aims and purposes of the foundations as written in the statutes. The answers of the problems were taken from the library and field research. The library research was done by perusing primary, secondary, and tertiary law materials with documents as their instruments. The field research was conducted by distributing questionnaire to the staff of the foundations and interviewing Notaries as the resource persons. After the research was done and conclusion was taken, it was founded that; the adjustment of the statutes of foundations has only been implemented by 27% of the respondents. The constraints of the adjustments of statutes of the foundations include the internal constraints, covering: the poor understanding upon the statutes, financial matters, the reluctance of the committee to the adjustments they should make, and the external constraints, which include the incomplete regulations, and the poor support from the involved parties. The foundations which establish Universities and Hospitals, or which hold Art Performing do not comply with Article 3 about foundation; whereas Foundations which run enterprises as indicated by Chapter 3 jo. Chapter 8 of the statutes of the foundations does not exceed 33.33 %.